2005
DOI: 10.1128/iai.73.9.6119-6126.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Domain II of Escherichia coli Dr Fimbriae Facilitates Cell Invasion

Abstract: Uropathogenic and diarrheal Escherichia coli strains expressing adhesins of the Dr family bind to decayaccelerating factor, invade epithelial cells, preferentially infect children and pregnant women, and may be associated with chronic or recurrent infections. Thus far, no fimbrial domain(s) that facilitates cell invasion has been identified. We used alanine scanning mutagenesis to replace selected amino acids in hydrophilic domain II of the structural fimbrial subunit DraE and evaluated recombinant mutant DraE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…An alternative model of internalization has proposed the involvement of the Dr adhesin in attachment and invasion of epithelial cells through its interaction with DAF (14,22,51). It has been demonstrated that the hydrophilic domain II of DraE and the complement control protein domain 3 and GPI anchor of DAF are critical for internalization of Dr ϩ E. coli (14,22,51). However, these studies have not directly addressed the role of adhesin recognition of CEACAM receptors in E. coli internalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative model of internalization has proposed the involvement of the Dr adhesin in attachment and invasion of epithelial cells through its interaction with DAF (14,22,51). It has been demonstrated that the hydrophilic domain II of DraE and the complement control protein domain 3 and GPI anchor of DAF are critical for internalization of Dr ϩ E. coli (14,22,51). However, these studies have not directly addressed the role of adhesin recognition of CEACAM receptors in E. coli internalization.…”
mentioning
confidence: 99%
“…Furthermore, conflicting data have been reported regarding the ability of laboratory strains expressing the Dr adhesin family operon afa-3 with inactivated afaD to invade HeLa cells (28,49). An alternative model of internalization has proposed the involvement of the Dr adhesin in attachment and invasion of epithelial cells through its interaction with DAF (14,22,51). It has been demonstrated that the hydrophilic domain II of DraE and the complement control protein domain 3 and GPI anchor of DAF are critical for internalization of Dr ϩ E. coli (14,22,51).…”
mentioning
confidence: 99%
“…However, binding to the decay-accelerating factor or carcinoembryonic antigen-related receptor of Dr family adhesins is mediated by the AfaE major subunit (31, 103,182,342,343). The distinction between major subunits involved in adhesion and minor subunits involved in invasion may not be so rigid for all Dr family adhesins, as the major subunit DraE has been implicated in facilitating cell invasion (68). Members of the Dr family are commonly present in diffusely adhering E. coli isolates associated with diarrhea or urinary tract infections (299).…”
Section: The ␥-Fimbriaementioning
confidence: 99%
“…The invasive region may involve selected amino acids in domain 2 (Lea et al, 1999;Anderson et al, 2004;Das et al, 2005). In light of the above results, future experiments will focus on analyses of the invasive abilities of chimeric fimbriae.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, agglutination of cells expressing DAF could be difficult to observe. Previous studies by Das et al (2005) showed that alanine substitutions for amino acids in the hydrophilic surface-exposed domain 2 did not affect the binding of the Dr adhesin to DAF. This suggests that the chosen insertion position of foreign epitopes localized from V28 to A38 of the DraE fimbrial subunit should not affect the bacterial adherence to DAF (Van Loy et al, 2002).…”
Section: Methodsmentioning
confidence: 99%